Different approaches to contracting in health systems - Jean Perrot (The World Health Organization, 2006)
Contracting is one of the tools increasingly being used to enhance the performance of health systems in both developed and developing countries; it takes different forms and cannot be limited to the mere purchase of services. Actors adopt contracting to formalize all kinds of relations established between them. A typology for this approach will demonstrate its diversity and provide a better understanding of the various issues raised by contracting. In recent years the way health systems are organized has changed significantly. To remedy the under-performance of their health systems, most countries have undertaken reforms that have resulted in major institutional overhaul, including decentralization of health and administrative services, autonomy for public service providers, separation of funding bodies and service providers, expansion of health financing options and the development of the profit or nonprofit private sector. These institutional reshuffles lead not only to multiplication and diversification of the actors involved, but also to greater separation of the service provision and administrative functions. Health systems are becoming more complex and can no longer operate in isolation. Actors are gradually realizing that they need to forge relations. The simplest way to do that is through dialogue, although some prefer a more formal commitment. Interaction between actors may take various forms and be on different scales. There are several types of contractual relations: some are based on the nature of the contract (public or private), others on the parties involved and yet others on the scope of the contract. Here they are classified into three categories according to the object of the contract: delegation of responsibility, act of purchase of services, or cooperation.